Inside Back Cover: Directional Transformation of Heterometallic Oxo Clusters: A New Approach to Prepare Wide‐Bandgap Cathode Interlayers for Perovskite Solar Cells (Angew. Chem. Int. Ed. 17/2023). Issue 17 (4th April 2023) - Xiao, Guo‐Bin; Mu, Xijiao; Zhou, Shuyu; Zhu, Liu; Peng, Yong; Liang, Qing; Zou, Xiaoxin; Zhang, Jian; Zhang, Lei; Cao, Jing
Abstract : A lead‐doped titanium‐oxo cluster protected by sulfur‐containing organic ligands is employed as a molecular model to realize the preparation of a PbSO4 –‐PbTi3 O7 heterostructure at the cathode interlayer in perovskite solar cells (PSCs), as reported by Yong Peng, Lei Zhang, Jing Cao, and co‐workers in their Research Article (e202218478) . The oxygen atoms from the sulfate ion in the heterostructure connect with iodine from the perovskite to boost interfacial electron extraction and reduce charge recombination. The efficiency and stability of the modified PSC are significantly improved.